Pengaruh Penerapan PSAK 72 terhadap Price Earning Ratio dengan Ukuran Perusahaan sebagai Variabel Kontrol - Listiyowati Listiyowati; Dwi Anie Mayasari (STIE Widya Manggala, 2021)
The application of PSAK 72 related to income in 2019 is very permissible because as a result of testing the effectiveness of financial decisions. This study aims to further examine the effect of PSAK 72 on price earning ratio with firm size as a control variable in Real Estate companies listed on the IDX in 2019. The sampling technique uses purposive sampling so that a sample of 35 companies is obtained. The statistical tool uses multiple linear regression. The results showed that the application of PSAK 72 had a significant positive effect on price earning ratio with a determination coefficient of 27.2%. And for the control variable, company size also had an influence on the price earning ratio by increasing the level of determination coefficient by 40.2%.